2022
DOI: 10.1136/jnnp-2022-328881
|View full text |Cite
|
Sign up to set email alerts
|

IVIg-exposure and thromboembolic event risk: findings from the UK Biobank

Abstract: BackgroundArterial and venous thromboembolic events (TEEs) have been associated with intravenous Ig use, but the risk has been poorly quantified. We aimed to calculate the risk of TEEs associated with exposure to intravenous Ig.MethodsWe included participants from UK Biobank recruited over 3 years, data extracted September 2020.The study endpoints were incidence of myocardial infarction, other acute ischaemic heart disease, stroke, pulmonary embolism and other venous embolism and thrombosis.Predictors included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In the ProDERM study, patients with known history of TEE were excluded; however, results from the overall analysis showed that patients with certain risk factors for TEEs were more likely to experience TEEs than those without. Similarly, a study of data from the UK Biobank from 502,492 individuals on IVIg found that the rate of TEEs was threefold higher in patients with a history of TEE than those without [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the ProDERM study, patients with known history of TEE were excluded; however, results from the overall analysis showed that patients with certain risk factors for TEEs were more likely to experience TEEs than those without. Similarly, a study of data from the UK Biobank from 502,492 individuals on IVIg found that the rate of TEEs was threefold higher in patients with a history of TEE than those without [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies seem to suggest that intravenous Ig is effective in DSP when dysimmunity is present, and ineffective if those patients are excluded; although, more head-to-head trials are needed to definitively address this contention, particularly given the recent negative randomised controlled trial. Given the high cost of intravenous Ig, logistic difficulties and rare adverse thrombotic events,117 a high priority is to determine which patient populations should be eligible. Early-onset small fibre neuropathy in children and young adults requires difficult decisions given that up to 90% of cases appear to have dysimmune/inflammatory contributors,118 and potential life-long consequences of non-treatment.…”
Section: Management Advancesmentioning
confidence: 99%
“…In terms of safety, in addition to the well-known adverse effects of IVIg, including nausea, headaches, and fever, venous thromboembolism (VTE) is of particular concern since both IVIg treatment and inflammatory myopathy may increase the risk for VTE. 13 16 In the ProDERM trial, six patients treated with IVIg experienced eight thromboembolic events (an incidence of 1.54 occurrences per 100 patient-months). This observation led to a protocol change in IVIg infusion rate in order to minimize thromboembolic incidence.…”
Section: Intravenous Immunoglobulin Use In Iimmentioning
confidence: 99%